Perbedaan Dampak Radioterapi dan Kemoterapi terhadap Fertilitas Penyintas Kanker Anak dan Remaja - Isnaini, Barkah; Allenidekania, Allenidekania (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify differences in the impact of chemotherapy and radiotherapy on the fertility of childhood and adolescent cancer survivors. The method used was a systematic review with searches in five databases including Pubmed, ScienceDirect, Scopus, Proquest, and Clinical Key Nursing regarding fertility in child and adolescent cancer survivors treated with chemotherapy or radiation, with a publication range from 2000 to 2018. There were 11,131 articles at the start of the data search, after filtering using the PRISMA 2020 method, the final results were 9 articles for analysis using the Joanna Briggs Institute (JBI) checklist. The nine articles used a cohort study involving a total of 25,210 respondents from six countries (America 2, Netherlands 2, Italy 2, Japan 1, England 1, Ireland 1). The research results show that alkylating agent type chemotherapy can affect the fertility of cancer survivors, as well as radiotherapy to certain areas of the body such as the abdomen, head and total body radiation also affect the fertility of childhood cancer survivors. In conclusion, providing appropriate information regarding the impact of alkylating agent chemotherapy and radiotherapy to the head area, abdomen and total body radiation before starting cancer therapy is very necessary. So that patients and families can make the best decisions in treating the patient's cancer regarding the patient's future. Key words: Adolescence, Chemotherapy, Childhood Cancer, Fertility, Radiotherapy